Vielä tahdon - Lahti, Virpi; Ekola, Hanna, 1961-; Jämsä, Kai; Päivä Osakeyhtiö (Hämeenlinna : Päivä, 2010)
1 kappale.
Virpi Lahti (lauluääni), yhtye.
Sanat tekstiliitteessä: suomi.
Keywords: Lahti, Virpi -- singlet; viihdemusiikki; iskelmät